Liquid Crystal Display (LCD) and Organic Light Emitting Diode (OLED) Applications on Natural Fibre Reinforced Polymer Matrix Composites. (26th November 2021) - Senthil Nayagam, V.; Anamika,; Gopinath, D.; Vetri Velmurugan, K.; Fathima, Rani; Joy Kinol, Mary; Alias Surendhar, Prasath; Christopher, David
Abstract : Natural materials are the alternative source for the manufacture of products due to environmental requirements. Hot injection moulding techniques make the composite product with fibreglass, granite waste filler, and polylactic acid (PLA). Five samples of each set and sampled with better hardness varied the volumetric percentage of glass fibre and the waste nanogranite particles. This effort is mainly concerned with evaluating the wear of dry sliding and friction of composites. Varying 15, 25, 35, and 45 N load, 750 and 1500 m sliding distance tested the composite materials, respectively. Parametric condition experiments were carried out at the stated process to record answers. Nanogranite composite materials are better than higher concentrations of glass fibre in PLA matrices composites, which are more resistant to wear and friction coefficients. The nanogranite powder is added with the filler element in the PLA matrix to provide a better coefficient of wear and rubbing. A high load of 45 N and a sliding distance of 1500 m were measured at low wear and low friction coefficients.